Positive Cytosolic 5-Nucleotidase 1A Antibodies in Motor Neuron Disease. Issue 1 (September 2020) - Assadi, Rami-James K.; Manousakis, Georgios
Abstract : Abstract: Inclusion body myositis (IBM) is the most common acquired myopathy in adults older than 50 years. Muscle biopsy remains the gold standard for diagnosis. Recently described serum antibodies against cytosolic 5-nucleotidase 1A (cN1A) are considered highly specific for IBM. However, positive cN1A antibodies in diseases other than IBM are recently reported. We review 2 cases in which serum antibodies were positive but ancillary testing revealed motor neuron disease. A 68-year-old man presented with asymmetric quadriceps and handgrip weakness prompting concern for IBM. However, electromyography showed purely chronic neurogenic abnormalities, and muscle biopsy was consistent with post-polio syndrome. A 60-year-old woman reported a history of progressive muscle weakness. Despite positive antibodies, examination and electromyography were indicative of amyotrophic lateral sclerosis. Serum cN1A antibodies are not 100% specific for the diagnosis of IBM. Careful clinical, electrophysiologic, and histopathologic correlation is required in workup of individuals with neuromuscular weakness and positive antibodies.